IN VITRO CYTOTOXIC ACTIVITY OF SECOISOLARICIRESINOL DIGLUCOSIDE ON HT-29, PA-1 CELL LINES, AND α-AMYLASE INHIBITORY ACTIVITY - DADDALA, GUNABHUSHANA; A, SWAROOPARANI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study was conducted to evaluate the in vitro cytotoxic activity and α- amylase inhibitory activity of secoisolariciresinol diglucoside (SDG). Methods: The cytotoxic activity was conducted on HT-29 (human colon cancer cell line) and PA-1 (human ovarian cancer cell line) by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay and the α- amylase inhibitory activity using acarbose as a standard. Both the tests were evaluated at different concentrations, 3.125–100 μg/ml and 50–2000 μg correspondingly and the concentration required for a 50% inhibition of viability (IC50) was determined graphically. The effect of the samples on the proliferation of HT-29 and PA-1 was expressed as the percentage cell viability. Results: SDG exhibited a considerable dose- and time-dependent inhibition on both HT-29 and PA-1 and also observed a concentration-dependent α-amylase inhibitory activity that leads in reduction of starch hydrolysis and hence eventually to lowered glucose levels. Conclusion: The present in vitro study concluded that SDG can be a potent anticancer and moderate hyperglycemic component.